THE INFLUENCE OF E-SERVICE QUALITY AND SITUATIONAL FACTOR ON CUSTOMER LOYALTY IN USING MANDIRI SYARIAH MOBILE APPLICATION DURING THE COVID-19 PANDEMIC - Amirah A; Sylvia Rozza; Aminah A (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2021)
This research aims to analyze the influence of e-service quality and situational factors on customer loyalty in using the Mandiri Syariah Mobile application during the Covid-19 pandemic. The method used in this research is quantitative. This research uses primary data collected through the questionnaires which were distributed to 100 respondents. They are customers of Bank Syariah Mandiri and users of the Mandiri Syariah Mobile application. The Customers have made complaints against the application. The results of the research using multiple linear regression tests showed that e-service quality and situational factors had a positive relationship. Partially, the e-service quality variable and situational factors have a positive and significant impact on customer loyalty in using the Mandiri Syariah Mobile application during the Covid-19 pandemic. The results of this research are expected to be useful for Bank Syariah Mandiri in developing strategies to increase customer loyalty. Keywords: E-Service Quality, Situational Factors, Customer Loyalty.